2019
DOI: 10.1002/pbc.27624
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic markers on parents' retention of pediatric oncology home care education: A pilot study

Abstract: Little is known about the extent to which parents retain the education on how to manage home medical emergencies. We sought to describe retention of pediatric oncology home care education (POHCE) in a cohort of 24 parents of newly diagnosed children with cancer and investigate sociodemographic disparities in this retention. We measured retention using a vignette‐based survey instrument. The mean score was 4 (range 0–6, SD = 1.6) and parents with high school only education and those with limited cancer health l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These constructs do not fully represent the range of skills required by a parent who must provide care to a child with cancer, which involves properly adhering to medication schedules, understanding infection risks, administering medications correctly, and recognizing when to seek emergent medical care (Haugen et al, 2016). In a systematic review, Hesselink et al (2022) reported inconsistent validity of the BHLS when tested against other more comprehensive measures of health literacy. Additionally, when using the NAAL, a more in-depth 28-item assessment of health literacy, investigators found that 46% and 48% of parents, respectively, failed to correctly perform at least one of two medication-related or immunization-related tasks (Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These constructs do not fully represent the range of skills required by a parent who must provide care to a child with cancer, which involves properly adhering to medication schedules, understanding infection risks, administering medications correctly, and recognizing when to seek emergent medical care (Haugen et al, 2016). In a systematic review, Hesselink et al (2022) reported inconsistent validity of the BHLS when tested against other more comprehensive measures of health literacy. Additionally, when using the NAAL, a more in-depth 28-item assessment of health literacy, investigators found that 46% and 48% of parents, respectively, failed to correctly perform at least one of two medication-related or immunization-related tasks (Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the BHLS, numerous tools can be used to assess health literacy, including the Cancer Health Literacy Test-6 (Dumenci et al, 2014), Rapid Estimate of Adult Literacy in Medicine (Davis et al, 1991), Shortened Test of Functional Health Literacy in Adults (Baker et al, 1999), National Assessment of Adult Literacy (NAAL; Yin et al, 2009), and the Newest Vital Sign (NVS; Weiss et al, 2005). In pediatric oncology, the BHLS (Sajeev et al, 2017), NVS (Shea et al, 2019), and Cancer Health Literacy Test-6 (Hentea et al, 2019) are the only standardized instruments, to our knowledge, that have been used to assess health literacy in parents of children with cancer. Similar to our findings, Hentea et al (2019) and Shea et al (2019) reported that 17% and 16.7% of parents of children with cancer, respectively, had low health literacy, while Sajeev et al (2017) reported that 32% of parents of children with cancer had low health literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation